Air permeability and drag crisis on high tech fabrics for cross country ski competitions - Oggiano, L.; Roar, S. L.; Morten, B. L.; Brian, H. (Procedia Engineering, 2012)
The present work aims to investigate possible improvements in cross country ski suits from an aerodynamic perspective with the main goal of evaluating if air permeability plays a significant role in the aerodynamic performances of the textiles. Three different fabrics with different surface pattern and different permeability were tested in a wind tunnel on cylinders with diameter 11 cm and 16 cm, for speeds ranging from 0 - 18m/s and with fabric strains from 0 - 65%. Air permeability tests were also carried out on all the different textiles for the same range of strains. Results show that significant drop in the drag coefficient can been obtained for critical wind speed (VCRIT) varying between 11m/s and 17m/s depending on textile type and stretch. A clear correlation between air permeability and drag crisis was not found leading to the conclusion that the surface deformation due to the stretching plays a major role if compared with the air permeability. The results obtained show that the lowest VCRIT(11 m/s) achieved in the experiments is above the relevant speeds in cross country skiing (4 - 9 m/s).